Characters Value in English Textbook - Sabetalia Sabetalia; Ayu Istiana Sari (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2023)
The purpose of the study was to analyze character values types in an English textbook, "Think globally act locally," for junior high school ninth graders. This study used descriptive qualitative research, using a 2018 textbook published by the Indonesian Ministry of Education. The study was conducted from June to July 2023. . The results showed that there are 9 types of character values, namely religiosity, hard work, creativity, curiosity, appreciation, friendliness, moral values, love to read, social awareness, and responsibility. The frequency of appearance friendliness moral values (64 times), love to read (32 times), social awareness (11 times), creativity and hard work (8 times), appreciation (5 times), curiosity (4 times), and religiosity and responsibility (3 times). These findings highlight the importance of character values in 21st century learning, particularly in the teaching of English as a Foreign Language (TEFL). In conclusion, this book already contains character values in it, although not all character values have been included in this textbook. Keywords: Characters Value, English Textbook, Descriptive Qualitative Research